Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.physbeh.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Repeated high-intensity interval exercise shortens the positive effect on executive function during post-exercise recovery in healthy young males

Abstract: A single bout of aerobic exercise improves executive function (EF), but only for a short period. Compared with a single bout of aerobic exercise, we recently found that high-intensity interval exercise (HIIE) could maintain a longer improvement in EF. However, the mechanism underlying the effect of different exercise modes on the modifications of EF remains unclear. The purpose of the current investigation was to test our hypothesis that the amount of exercise-induced lactate production and its accumulation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 47 publications
9
84
5
1
Order By: Relevance
“…First, we showed that the deterioration of cognitive function during hypoglycemia was less after HIIT than rest, which is in accordance with previous studies that infused lactate during hypoglycemia (10; 12). In addition, a recent exercise study found that higher lactate levels after HIIT were associated with better executive function during post-exercise recovery, under euglycemic conditions (41). We also observed fast suppression of hypoglycemic symptoms, cortisol and growth hormone responses after HIIT (i.e.…”
Section: Discussionsupporting
confidence: 71%
“…First, we showed that the deterioration of cognitive function during hypoglycemia was less after HIIT than rest, which is in accordance with previous studies that infused lactate during hypoglycemia (10; 12). In addition, a recent exercise study found that higher lactate levels after HIIT were associated with better executive function during post-exercise recovery, under euglycemic conditions (41). We also observed fast suppression of hypoglycemic symptoms, cortisol and growth hormone responses after HIIT (i.e.…”
Section: Discussionsupporting
confidence: 71%
“…Given the proposed influence of cerebral lactate metabolism on cognition (Tsukamoto et al . ; Hashimoto et al . ), the increase in cerebral lactate delivery with thermal stress at high altitude may explain the maintenance of cognitive performance in the face of reduced CDO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…high-intensity exercise the brain becomes dependent on lactate delivery (13,18), and repeated high-intensity interval exercise (HIIE), which attenuates the increase in blood lactate, results in impaired maintenance of HIIEenhanced EF (19). Both cognitive tasks and exercise increase neuronal activity and energy demand (10,20,21), and high-volume exercise with sufficient intensity and duration prolongs the exercise-induced improvement in EF (22).…”
mentioning
confidence: 99%
“…We explored the relationship between exercise-induced lactate production and improved cognitive function (19) and used HIIE, which is emerging as an alternative to current health-related exercise guidelines (30). However, the impact of HIIE on the cerebral vasculature (30) and its implication for cognitive function are not established.…”
mentioning
confidence: 99%